Factors Affecting Supplier Integration in Selected County Governments in Lake Nyanza Region - Obegi, Elizabeth Kwamboka; Juma, Dennis (International Journal of Supply Chain and Logistics, 2025)
Purpose: The purpose of this study was to investigate the factors influencing supplier integration in selected County Governments within the Lake Nyanza Region of Kenya. The study was guided by four specific objectives: to examine the influence of environmental uncertainty, availability of technological resources, supply chain relationships, and organizational structure on supplier integration. Methodology: A descriptive research design was adopted, targeting 106 procurement and supply chain staff across selected counties, with a 92% response rate. Data was collected using structured questionnaires and analyzed using both descriptive and inferential statistics, including correlation and multiple regression analysis. Findings: The findings revealed that all four variables had a positive and statistically significant influence on supplier integration. Organizational structure and technological resources emerged as the most influential factors, followed by environmental uncertainty and supply chain relationships. The study concluded that successful supplier integration requires a multi-dimensional approach involving structural alignment, technological investment, environmental adaptability, and strong relational networks. Unique Contribution to Theory, Policy and Practice: The study recommends that county governments strengthen internal organizational frameworks, enhance technological infrastructure, and establish long-term collaborative relationships with suppliers. In addition, counties should adopt strategic mechanisms to manage environmental uncertainties that hinder procurement efficiency. Further research is suggested to explore the role of political governance, supplier perspectives, and longitudinal integration outcomes.